Actively demonstrating library expertise in a research assessment exercise. Issue 1 (12th January 2015) - Wong, Gabrielle Ka Wai; Caplan, Victoria F.; Chan, Diana L. H.; Fung, Lois M. Y.; Lam, K.T.
Abstract : Purpose: – The purpose of this paper is to describe HKUST Library's active participation in helping the university prepare for the 2014 Research Assessment Exercise (RAE 2014) in Hong Kong. Through the process the authors demonstrated library's value and librarians' expertise in supporting research. Design/methodology/approach: – This is a case study that highlights how HKUST Library tackled this complex exercise. The effort was delineated as three stages: the design stage when the authors proactively supported the electronic system design for RAE 2014, the formation stage in which the submission infrastructure was built, and the data process stage. Findings: – Based on the Library's experience in creating and managing the Institutional Repository and the Scholarly Publication Database, the participation proved to be instrumental in designing and building the electronic infrastructure for the RAE 2014. After the project, the HKUST research community had higher trust and regard of the Library, both for the research information management systems and librarians' expertise in providing research support service. Practical implications: – The paper elaborates details of HKUST Library's effort, including human resource deployment, project management strategy, operational tactics, challenges the authors faced and keys to success. The experience demonstrates that libraries and librarians can establish credibility and gain respect from research communities through delivering tangible outcomes. Originality/value: – There is very few case studies in the literature on libraries' participation in and contribution to RAEs. This paper fills a gap in the area.